2016
DOI: 10.1002/adfm.201603843
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Enhanced Selective Surface Deposition of Polymer‐Based Fragrance Delivery Systems

Abstract: Surface deposition is a critical step in the application of fragrance‐containing products. This contribution presents a novel strategy to enhance the deposition of polymer‐based fragrance delivery systems onto cotton substrates from the application medium using phage display identified peptides. Following the identification of cotton binding peptide ligands under fabric softening conditions via phage display, the strongest binding peptide ligand is incorporated into two model polymer‐based fragrance delivery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The surface deposition of fragranced products is an important parameter that determines the long-lastingness of fragrance perception. [48][49][50] We thus examined the adhesion of fragranceloaded nanoparticles to the silk fabric and their washing durability. Fig.…”
Section: Deposition Of Nps On the Fabric Surfacementioning
confidence: 99%
“…The surface deposition of fragranced products is an important parameter that determines the long-lastingness of fragrance perception. [48][49][50] We thus examined the adhesion of fragranceloaded nanoparticles to the silk fabric and their washing durability. Fig.…”
Section: Deposition Of Nps On the Fabric Surfacementioning
confidence: 99%
“…As is known, surface deposition is a critical step in the use of fragrance‐containing materials. Recently, a conceptually novel work on the surface deposition was reported by Günay et al . This study specifically aims at enhancing the substrate deposition of polymer‐based fragrance delivery systems.…”
Section: Other Strategies For Improving Functionality Of Microcapsulementioning
confidence: 99%
“…Within the last decade, a variety of peptide sequences have been identified that bind strongly, sequence specifically or even material specifically to their target surface. Examples of interesting material surfaces are numerous and range, e.g., from synthetic polymer materials, to lignin, cellulose, cotton, hair, zinc oxide, gadolinium oxide, inorganic semiconductors, ferromagnetic materials, hydroxyapatite, titanium to noble metals …”
Section: Identification Of Functional Peptide Sequencesmentioning
confidence: 99%